Planning the Electron Traffic in Semiconductor Networks: A Mesoscopic Analog of the Braess Paradox Encountered in Road Networks - Baltazar-Rojas, S (American Institute of Physics, 2013)
By combining quantum simulations of electron transport and scanning-gate microscopy, we have shown that the current transmitted through a semiconductor two-path rectangular network in the ballistic and coherent regimes of transport can be paradoxically degraded by adding a third path to the network. This is analogous to the Braess paradox occurring in classical networks. Simulations reported here enlighten the role played by congestion in the network. © 2013 AIP Publishing LLC.